Using VARK Approach for Assessing Preferred Learning Styles of First Year Medical Sciences Students: A Survey from Iran - Hadi Peyman; Jamil Sadeghifar; Javaher Khajavikhan; Masood Yasemi; Mohammad Rasool; Yasemi Monireh Yaghoubi; Monireh Mohammad Hassan Nahal; Hemati Karim (Journal of Clinical and Diagnostic Research, 2014)
Background: Preferred learning styles of learners are different, which depend on tastes, mentality preparedness, as well as physical condition, in terms of sensory modalities. Identifying and employing appropriate learning styles could play an important role in selecting teaching styles, which can improve education ultimately. Aim: The present study aimed to assess the diversity of learning styles amongst medical students of a medical sciences university which was located west of Iran, in 2010. Methods: A cross-sectional study which employed VARK learning style’s questionnaire was done on 141 first year medical sciences students at Ilam University of Medical Sciences in 2010. Data was collected with use of VARK questionnaire. The validity of the questionnaire was assessed on basis of experts’ views and its reliability was calculated by using Cronbach’s alpha coefficients (α=0.86). Data were analysed by using SPSS software and Chi-square test. Results: Overall, 41.6% of the samples preferred to use a single learning style (Uni-modal). Of these, 17.7% preferred the Aural style, 17% preferred Reading and Writing, 6.4% preferred Kinesthetic style and 0.7% preferred Visual styles. Among the rest of the 82 students who preferred more than one style (multimodal), 17% chose two modes (bimodal), 13.5% chose three modes (tri-modal), and 27.6% chose four modes (quad-modal). There was a significant difference between educational levels and majors on one hand and choice of quad modal of VARK styles on the other hand (p=0.008). A significant association was also found between participants’ genders and selection of visual and reading/writing styles (p=0.03). Conclusion: The preferred learning styles of medical students in the present study were aural and reading/writing. It is suggested that all medical students must be tested to determine their desired learning styles by using VARK questionnaire, also to choose appropriate teaching methods and to improve educational goals.